2004
DOI: 10.12968/ijpn.2004.10.12.17279
|View full text |Cite
|
Sign up to set email alerts
|

A time to pause

Abstract: The close of the year is here and this offers us a time to reflect on the directions taken in palliative care. The year has been a good one for the journal with the quality of papers always increasing and the editorial team would like to thank all of our readers and authors for their consistent support and offer our best wishes for a safe and festive Christmas break. The introduction of commentaries and other forms of debate in the journal offers us an opportunity to reflect on our work and consider the ways f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…for colonies counted from triplicate plates under each condition the nuclear c-Abl protein can contribute to the induction of apoptosis (Sawyers et al, 1994). Since Kharbanda et al (2000) have reported that c-Abl protein is directly associated with hTERT and inhibits telomerase activity, imatinib in combination with telomestatin may affect the dynamic regulation of telomeres. This observation suggests that combined use of telomerase inhibitors and imatinib or other chemotherapeutic agents may be a very useful approach to treatment of BCR-ABL-positive leukemia (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…for colonies counted from triplicate plates under each condition the nuclear c-Abl protein can contribute to the induction of apoptosis (Sawyers et al, 1994). Since Kharbanda et al (2000) have reported that c-Abl protein is directly associated with hTERT and inhibits telomerase activity, imatinib in combination with telomestatin may affect the dynamic regulation of telomeres. This observation suggests that combined use of telomerase inhibitors and imatinib or other chemotherapeutic agents may be a very useful approach to treatment of BCR-ABL-positive leukemia (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…Human telomeric DNA coimmunoprecipitated with hTERT antibody (Vaziri et al, 1999;Fu et al, 2000;Kharbanda et al, 2000;Wood et al, 2001) on in vivo crosslinking was performed by the standard procedure described previously (Braunstein et al, 1993;Hsu et al, 1999). Immunoprecipitated (IP) DNA was placed onto a membrane by using a dot-blotting apparatus and then hybridized with 32 P-labeled DNA probe.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…Moreover, inhibition of c-Abl with STI571 treatment has been shown to block araC-induced apoptosis (34). c-Abl interacts with diverse signaling molecules that are associated with the apoptotic response (17,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32); however, there has been no known interaction between c-Abl and the initiator or effector caspases. In the present studies, the functional significance of the c-Ablcaspase-9 interaction in cells is supported by the demonstration that inhibition of c-Abl with STI571 blocks autoprocessing of caspase-9 to the p35 subunit.…”
Section: C-abl Regulates Caspase-9 Autocleavagementioning
confidence: 99%